The benefits of participation in school extra music activities as seen by Hong Kong primary school students Aged 9-12 - Hui, Suet Fun (2022)
Instrumental music is one of the extra-curricular activities that students may join after school hours to acquire more music experience. There is limited number of studies in Hong Kong investigating the effect of group instrumental music training on primary school children. The impact of school-based music training on both academic and psychological issue is not well understood. This research aims at revealing the reasons that make students participate in these extra-curricular music activities, the benefits that students perceive in the music activities and how these music activities affect their aspiration in learning. This research focuses to investigate deeply in one context of a primary school in Hong Kong of the real life experience of students aged 9-12 about the above issue.